Utilization of mulberry leaf meal (Morus alba) as protein supplement in diets for laying hens - Al-Kirshi, Riyadh Abbas; Alimon, Abdul Razak; Idrus, Zulkifli; Sazili, Awis Qurni; Mohamed, Wan Zahari; Ivan, Michel (PAGEPress, 2010)
A 12-week feeding experiment was conducted to study the effects of inclusion of 0 (control; Diet A), 10% (Diet B), 15% (Diet C) and 20% (Diet D) of mulberry leaf meal (Morus alba) in the diet on production performance and egg quality of laying hens. Feeding mulberry leaf meal (MLM) reduced (P<0.05) the feed intake, egg production, egg weight and egg mass. However, feed conversion ratio was not affected (P>0.05). Shell weight and yolk weight were decreased (P<0.01), but shell thickness and albumen weight were not affected (P>0.05). Haugh units increased (P<0.001) as the level of MLM increased. Also, feeding MLM improved (P<0.001) the yolk color when compared with control. The results indicated the possibility of including up to 10% of mulberry leaf meal in diets of egg laying hens without adversely affecting the performance and egg quality.